Antibodies to MOG and AQP4 in adults with neuromyelitis optica and suspected limited forms of the disease. (June 2015) - Höftberger, Romana; Sepulveda, María; Armangue, Thaís; Blanco, Yolanda; Rostásy, Kevin; Cobo Calvo, Alvaro; Olascoaga, Javier; Ramió-Torrentà, Lluís; Reindl, Markus; Benito-León, Julián; Casanova, Bonaventura; Arrambide, Georgina; et al.
Objective: We aimed to report the frequency and implications of antibodies to myelin oligodendrocyte glycoprotein (MOG-ab) in adults with demyelinating syndromes suspicious for neuromyelitis optica (NMO). Methods: Samples from 174 patients (48 NMO, 84 longitudinally extensive myelitis (LETM), 39 optic neuritis (ON), and three acute disseminated encephalomyelitis (ADEM) who presented initially with isolated LETM) were retrospectively examined for AQP4-ab and MOG-ab using cell-based assays. Results: MOG-ab were found in 17 (9.8%) patients, AQP4-ab in 59 (34%), and both antibodies in two (1.1%). Among the 17 patients with MOG-ab alone, seven (41%) had ON, five (29%) LETM, four (24%) NMO, and one (6%) ADEM. Compared with patients with AQP4-ab, those with MOG-ab were significantly younger (median: 27 vs. 40.5 years), without female predominance (53% vs. 90%), and the clinical course was more frequently monophasic (41% vs. 7%) with a benign outcome (median Expanded Disability Status Scale: 1.5 vs. 4.0). In eight patients with paired serum-cerebrospinal fluid (CSF) samples, five had MOG-ab in both samples and three only in serum. Antibody titres did not differ among clinical phenotypes or disease course. MOG-ab remained detectable in 12/14 patients (median follow-up: 23 months) without correlation between titres' evolution and outcome. Conclusion: MOG-ab identify a subgroup of adult patients with NMO, LETM and ON that have better outcome than those associated with AQP4-ab. MOG-ab are more frequently detected in serum than CSF and the follow-up of titres does not correlate with outcome.